Mental health care in primary care: A cartography - Santana, Taís Fernanda Maimoni Contieri; Pereira, Maria Alice Ornellas [UNESP] (Universidade de Estado do Rio de Janeiro, 2018)
Objective: To map the daily care of patients with psychic disorders, the subjects of the mapping being the personnel of a family health unit and a family health support unit. Method: Nine health professionals participated in this qualitative study in northwest São Paulo in mid-2013. Data were collected by case study, field diary, semi-structured interview and analytical flowchart. The project was approved by the research ethics committee. Results: Results were captured and structured in three territories, of which the territory of doing was presented in this study. These evidenced the difficulties facing possible reversal of care, which is still based on the hegemonic medical model. Conclusion: There were obstacles to effective bonding, accountability and commitment by these professionals, making it hard to envisage advances in daily mental health practice, which hinders psychosocial rehabilitation.
El cuidado en salud mental en la atención básica: Una cartografía
O cuidado em saúde mental na atenção básica: Uma cartografia
Keywords: Empathy; Geographic mapping; Mental health; Primary health care